2022
DOI: 10.3390/jof8101026
|View full text |Cite
|
Sign up to set email alerts
|

A First Draft of the Core Fungal Microbiome of Schedonorus arundinaceus with and without Its Fungal Mutualist Epichloë coenophiala

Abstract: Tall fescue (Schedonorus arundinaceus) is a cool-season grass which is commonly infected with the fungal endophyte Epichloë coenophiala. Although the relationship between tall fescue and E. coenophiala is well-studied, less is known about its broader fungal communities. We used next-generation sequencing of the ITS2 region to describe the complete foliar fungal microbiomes in a set of field-grown tall fescue plants over two years, and whether these fungal communities were affected by the presence of Epichloë. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…(e.g., Bastías, Bustos, et al, 2022;Liu, Tang, et al, 2022). This is also in agreement with another experimental findings that showed that Epichloë altered root-associated bacterial communities and shoot-or root-associated fungal communities (Jin, Wang, et al, 2023;Nissinen et al, 2019;Rasmussen et al, 2023;Zhong et al, 2018) (but see e.g., Dale & Newman, 2022). Our results showed that the most substantial Epichloë-based changes in bacterial composition occurred at Days 14 and 28 post-GA treatment.…”
Section: Discussionsupporting
confidence: 92%
“…(e.g., Bastías, Bustos, et al, 2022;Liu, Tang, et al, 2022). This is also in agreement with another experimental findings that showed that Epichloë altered root-associated bacterial communities and shoot-or root-associated fungal communities (Jin, Wang, et al, 2023;Nissinen et al, 2019;Rasmussen et al, 2023;Zhong et al, 2018) (but see e.g., Dale & Newman, 2022). Our results showed that the most substantial Epichloë-based changes in bacterial composition occurred at Days 14 and 28 post-GA treatment.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with our previous study, where Epichloë symbiosis in tall fescue ( Schedonorus phoenix ) impacted only the endophytic fungal community in leaves, not the bacterial community [ 38 ]. However, Epichloë symbiosis in tall fescue have also been reported not to impact foliar fungal community structures [ 39 ]. Significant differences in the structures of fungal communities were observed in the dataset, with and without depleting Epichloë taxa and, hence, confirming the role of Epichloë in shaping the endophytic mycosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Epichloë in perennial ryegrass ( Lolium perenne ) did not significantly affect fungal community structure [ 37 ], but Epichloë in tall fescue ( Festuca arundinaceae = Schedonorus phoenix) altered the community of fungal endophytes, but not the bacterial endophytes, in leaves of the host plants [ 38 ]. In another study, the foliar fungal communities in S.phoenix were not different between Epichloë -symbiotic and Epichloë -free plants, but the fungal community structures between the two consecutive sampling years differed [ 39 ]. In Festuca rubra , the presence of Epichloë festuca along with the habitat of the host plant affected the infection frequencies of nonsystemic fungal endophytes [ 40 ].…”
Section: Introductionmentioning
confidence: 99%